Do consumers choose the right credit contracts? - Sumit Agarwal; Souphala Chomsisengphet; Chunlin Liu; Nicholas S. Souleles (Goethe University Frankfurt, Center for Financial Studies (CFS), 2005)
A number of studies have pointed to various mistakes that consumers might make in their consumption-saving and financial decisions. We utilize a unique market experiment conducted by a large U.S. bank to assess how systematic and costly such mistakes are in practice. The bank offered consumers a choice between two credit card contracts, one with an annual fee but a lower interest rate and one with no annual fee but a higher interest rate. To minimize their total interest costs net of the fee, consumers expecting to borrow a sufficiently large amount should choose the contract with the fee, and vice-versa. We find that on average consumers chose the contract that ex post minimized their net costs. A substantial fraction of consumers (about 40%) still chose the ex post sub-optimal contract, with some incurring hundreds of dollars of avoidable interest costs. Nonetheless, the probability of choosing the sub-optimal contract declines with the dollar magnitude of the potential error, and consumers with larger errors were more likely to subsequently switch to the optimal contract. Thus most of the errors appear not to have been very costly, with the exception that a small minority of consumers persists in holding substantially sub-optimal contracts without switching.
urn:nbn:de:hebis:30-23443
Keywords: G11; G21; E21; E51; 330; Consumption-Saving; Borrowing; Consumer Finance; Consumer Credit; Credit Cards; Banking; Verbraucherkredit; Konsumentenverhalten; Kreditkarte; Test; USA